COMMUNITY PARTNERSHIP THROUGH AN ARTIST DRIVEN,COLLABORATIVE PROJECT BETWEEN LEARNERS FROM THE RIDGE SCHOOL AND SALVAZIONE CHRISTIAN SCHOOL - Schulz, Kathrin Marion (My University, 2006)
A Community Partnership Art Event, resulting from curating and facilitating an educational collaboration was held on the 23 March 2004, ten years into South Africa’s democracy. Through a Masters in Fine Arts coursework entitled “Creating, Curating and Critiquing” offered at the University of Witwatersrand, I attempted to test the boundaries of the Arts and Culture Learning Area and explore alternatives to the current definition of “outreach”. The grade six learners from The Ridge School, an independent boys’ preparatory school and Salvazione Christian School, an assisted government school, were brought together over a period of ten weeks during regular school art lessons. Through the guidance and expertise of various artists, workshops were cocoordinated with the collaborative ideas of the learners coming to the fore. The process and dialogue established between learners, artists and educators was intended to shift my own parameters of teaching primary school art. Focusing on people rather than the final products points to a readiness to view knowledge not as a commodity owned bthe expert teacher, but rather as something which can be constructed and developed with the learners. Originally the collaboration was intended as a celebration of the opening of new premises for Salvazione Christian School. The public art happening was held in a tent next to the informal settlement where a large majority of the children from Salvazione Christian School live. 3 Rather than what might be described as a modernist approach to art education, where the focus seems to be on the artist and artwork, the focus was on linking art to social interaction, and it was through the discovery of a form of hybridity that a number of differences between the two communities were challenged and exposed. This resulted in an approach that seems similar to the manner in which the Indian writer, Salman Rushdie writes of hybridity: “Hybridity, impurity, intermingling, the transformation that comes of new and unexpected combinations of human beings, cultures, ideas, politics, movies, songs.” (Coombes, 2000:39) Through this hybridity tensions were created and explored rather than a ‘rainbow’ or melting pot created, where differences are glossed over as in a multicultural approach. The primary research methodology was participant observation in which directly observed data was analyzed and interpreted. Data was gathered from the interactions in the workshops, setting up the exhibition and the art event. As intended, a link between art and ‘outreach’ was established. In order for this link to change into a community partnership, it must be seen as part of a much longer process. The process as a whole did become a different kind of primary school art space, preparing the way for possible positive transformation of the visual arts in the arts and culture learning area at primary school level.
Master of Arts in Fine Arts - Fine Arts
Keywords: community; artist; school; learners; art event; artists-in-school; curating; dialogue; hybridity; participant observation; site-specific; witnessing